The Lived Experience of Grief and Hope Among Mothers After the Loss of Their First Child: A Phenomenological Study - Sindi Sariani; Rita Eka Izzaty (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The loss of a child represents one of the most profound and life-altering experiences for parents, particularly mothers who often hold deep emotional and psychological bonds with their children. This study aims to explore the lived experiences of grief and hope among mothers following the loss of their first child. Using a qualitative phenomenological approach, data were collected through semi-structured in-depth interviews with four mothers who had experienced the loss of their first child. The findings reveal that grief emerges as a complex and dynamic process characterized by shock, emotional distress, anger, and gradual acceptance. At the same time, hope gradually develops through reflective meaning-making, role reorientation within the family, and spiritual engagement. The coexistence of grief and hope illustrates that psychological recovery after loss does not eliminate sorrow but allows individuals to live meaningfully alongside it. These findings highlight the importance of psychosocial and counseling support to assist bereaved mothers in reconstructing meaning and sustaining emotional resilience after profound loss.